Ethnolinguistic Identities and Language Revitalisation in a Small Society: The Case of the Faroe Islands - Pax Leonard, Stephen (Umeå University Library, 2011)
This article explores how Faroese managed to be revitalised from a threatened, minority language to become the main language of 45,000 people living on seventeen islands in the North Atlantic. The Faroese language was coupled with a rich oral literature and was spoken in a very narrow and welldefined diglossic context which localised a Faroese linguistic identity. The social space of the homestead was not linguistically infringed upon by the colonial language, Danish, and was left in fact to survive in an environment of thriving spoken traditions. It is argued that these factors and the choice of an orthography quite distinct from the competing variety, enabled the language to survive. Faroese shows us that a tiny language can survive for centuries against the odds, providing certain conditions are in place. It is also evidence of how a low variety in a stable diglossic situation can flourish when the linguistic status quo is dismantled. Faroese has gradually moved into the high variety domain, squeezing Danish out. In theory, the revitalisation of Faroese would appear to be a model of success. Regrettably, the ingredients of language planning success are complex, culture-specific and do not seem to lend themselves to broad reapplication.